Analysis of Extreme Weather in the Waters of West Kalimantan using the WRF-ARW Model (Case Study 13-14 July 2021) - Tarisya Juliana; Riza Adriat; Randy Ardianto; Andi Ihwan; Yuris Sutanto (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2026)
On 13 July 2021, there was an extreme weather phenomenon in the waters of West Kalimantan. The extreme weather resulted in several fishing boats sinking and causing 136 casualties. This study aims to analyze atmospheric conditions during extreme weather on July 13-14, 2021. In running the WRF-ARW model, verification is carried out using the dichotomy method (Accuracy, POD, FAR) and RMSE to determine the model's accuracy in simulating extreme weather events. The RMSE verification results show an error value of 4,97. The results of the WRF-ARW model output show that the extreme weather that occurs is caused by the presence of a convergence wind zone with a maximum wind speed of 18 m/s, causing the formation of cumulonimbus clouds. OLR simulations show a low value of 122 watts/m², indicating a lot of cloud cover with the potential for rain. The emergence of this convection zone causes strong winds, which cause high waves, thus contributing to ship accidents.